Collaborative forum on genetic testing and gene therapy engages year 2 medical students - Abdul Rahman, Amirah; Al-Khateeb, Alyaa R. Mahmood; Ab. Rahim, Sharaniza (Faculty of Medicine, 2025)
Lecturers from the Department of Biochemistry & Molecular Medicine, Faculty of Medicine, recently hosted an engaging session of the Collaborative Group for Collaborative Teaching (CGCT) for the MED212 Reproductive System module on May 8, 2025. The module encompassed two biochemistry and molecular medicine lectures delivered by Assoc. Prof. Dr. Sharaniza Ab. Rahim and Assoc. Prof. Dr. Alyaa R. Mahmood Al-Khateeb